REPRESENTATION OF THE AUTHOR’S PERSONAL WORLDVIEW IN A LITERARY TEXT - Kamola M. Abdulloeva; Na. Sahm IL (Journal Park Publishing, 2025)
This article explores the most essential element of literary text—the monologue—and its unique features from cognitive, linguocultural, and linguistic perspectives. Special attention is given to the importance of reflecting the author’s conceptual worldview in the monologue. Additionally, the similarities and differences between dialogue and monologue are analyzed based on theoretical grounds.
Keywords: Subjective attitude, cognitive functions, mutual influence, multifunctionality.